2017
DOI: 10.1002/cta.2392
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and calculation of critical inductance and output voltage ripple of a simple non‐isolated multi‐input bidirectional DC‐DC converter

Abstract: Summary In this paper, a simple non‐isolated multiple input (MI) bidirectional DC‐DC topology is proposed which can operate in buck, boost, or buck‐boost modes. The proposed topology utilizes a battery pack to realize the bidirectional power flow operation especially when the input sources are non‐storable ones. The excess energy of input sources can be stored in the battery and be injected to the load, when required. Simultaneous or independent power transfer of input sources is also provided. For better eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…The volt-second balance principle is applied on inductors to achieve the gain relationship. 23,24 F I G 3 Key waveforms of proposed topology during A, continuous conduction mode (CCM) and B, discontinuous conduction mode (DCM) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Ideal Voltage Gain Calculationmentioning
confidence: 99%
“…The DC-DC converters can be categorized to isolated or nonisolated, coupled or noncoupled inductor-based topologies. [8][9][10] This paper concentrates only on nonisolated noncoupled-inductor-based topologies (NINCITs). Usually, the conventional NINCITs produce medium/low voltage gains, 11 but recently, many NINCITs have been presented that are capable of producing large boosting factors.…”
Section: Introductionmentioning
confidence: 99%